Polemics and Patronage in the City of Victory Vyasatirtha, Hindu Sectarianism, and the Sixteenth-Century Vijayanagara Court - Stoker, Valerie (University of California Press, 2016)
How did the patronage activities of India's Vijayanagara Empire (c. 1346-1565) influence Hindu sectarian identities? Although the empire has been commonly viewed as a Hindu bulwark against Islamic incursion from the north or as a religiously ecumenical state, Valerie Stoker argues that the Vijayanagara court was selective in its patronage of religious institutions. To understand the dynamic interaction between religious and royal institutions in this period, she focuses on the career of the Hindu intellectual and monastic leader Vyasatirtha. An agent of the state and a powerful religious authority, Vyasatirtha played an important role in expanding the empire's economic and social networks. By examining his polemics against rival sects in the context of his work for the empire, Stoker provides a remarkably nuanced picture of the relationship between religious identity and sociopolitical reality under Vijayanagara rule. "Valerie Stoker's work, with its insightful analysis of the role played by the Madhva sectarian leader Vyasatirtha in the complex and multifaceted interplay of religion and state patronage in sixteenth-century South India, is a valuable addition to the corpus of writings on Vijayanagara." -ANILA VERGHESE, author of Religious Traditions at Vijayanagara "Never have Hindu philosophical debates and sectarian disputes seemed so lively and so relevant to historical dynamics." -LESLIE C. ORR, author of Donors, Devotees and Daughters of God: Temple Women in Medieval Tamilnadu "Stoker sets a new standard for the study of religion in early modern South India, recognizing that doctrine does not unfold in a sociopolitical vacuum and providing an insightful account of the relations between sectarian organizations and their political patrons." -PHILLIP B. WAGONER, Wesleyan University "In this engrossing and sophisticated book, Stoker brings together fine narrative fluency, careful scholarship across different disciplines, and critical sympathy for ideas and people from a different time and place." -CHAKRAVARTHI RAM-PRASAD, author of Divine Self, Human Self: The Philosophy of Being in Two Gita Commentaries VALERIE STOKER is Associate Professor of South Asian Religions and Director of the Master of Humanities Program at Wright State University in Dayton, Ohio.